Assessment of COVID-19 related preventive measures in medical students across a lower-middle-income country: A cross-sectional study from Pakistan. (October 2022) - Ahmad, Shoaib; Hassan, Sheza; Farooq, Umar; Ahmad, Shkaib; Ehsan, Sumera; Ali, Daniyal Mansoor; Essar, Mohammad Yasir; Khan, Hamza Farooq; Hashim, Hashim Talib
Abstract: Objectives: This study aims to identify the effect of having COVID-19 positive close contact on practices and evaluate practices regarding COVID-19 prevention among medical students and the differences among clinical and preclinical students. Study design: The cross-sectional study included medical students from the Micro-fest++ event held on 30th May 2020. Methods: Participants filled a questionnaire of 15 questions regarding COVID preventive measures practices having satisfactory reliability (Cronbach's alpha = 0.715) and validity. The Statistical Package for Social Sciences (IBM SPSS) 26.0 was used for data analysis. Out of 1342 medical students, the majority were female (N = 881, 65.6%). Greater proportion (47%) of students had good practices (>85.7%) (p < 0.05). Results: Having COVID-19 positive relatives resulted in higher positive responses for practices with 11.86 ± 1.94 (out of 14) compared to 11.78 ± 2.38 for the COVID-19 negative group. Clinical year students compared to preclinical students responded positively to all questions, except one, and had a better score of 11.90 ± 2.28 (out of 14) compared to 11.61 ± 2.37 (p < 0.05). A significant difference was noted for "Information on preventive measures" (p < 0.01), "Avoiding crowds and staying home" (p < 0.05), "Social distancing (maintain 3 feet)" (p < 0.01), and "Practices of disinfection after going outside" (p < 0.05). Conclusions: Overall, medical students showed good practices, but a lack of knowledge in certain areas requires addressing infection during clinical rotations. A greater proportion of clinical students and those having a COVID-19 positive relative showed better adherence to practices. Highlights: Having COVID-19 infected relatives had a positive impact on preventive measures. Clinical year students responded positively compared to preclinical ones. Gap of preventive practices was highly evident amongst both groups.